Physiological and behavioral responses of laying hens exposed to long-term high temperature. (July 2021) - Kim, Da-Hye; Lee, Yoo-Kyung; Lee, Sung-Dae; Kim, Sang-Ho; Lee, Kyung-Woo
Abstract: The present study was conducted to investigate the impact of a 42 d period of heat stress on laying hens with respect to rectal temperature, body-surface temperature, heart rate, heterophil to lymphocyte ratio (H/L ratio), corticosterone (CORT) in plasma and yolk samples, and video-assessed behaviors. A total of one hundred twenty 56-week-old ISA-brown laying hens were continuously exposed to one of three temperature regimes: optimal (LT; 22 °C), moderate (MT; 27 °C), and high (HT; 32 °C). The relative humidity was maintained at 50% in all treatments. HT vs. MT and LT increased rectal temperature, heart rate, and body-surface temperature on all days (P < 0.05). HT vs. LT raised (P < 0.05) the H/L ratio in blood at day 42 following heat exposure. On the other hand, both HT- and MT-exposed laying hens had higher (P < 0.05) plasma CORT compared with those on LT group only at 28 and 42 d following heat treatment. Yolk CORT was elevated (P < 0.05) in the HT vs. MT and LT groups at 3 and 14 d following heat treatment. Panting and wing elevation were the most relevant behaviors in laying hens exposed to HT vs. MT and LT. The study shows that rectal and body-surface temperature, heart rate, and behavior, but not CORT or H/L ratio, are the reliable indicators for assessing the stress status of laying hens over extended period of heat stress. Highlights: High, but not moderate or low ambient temperature clearly altered physiological and behavioral responses in laying hens. Heterophil/lymphocyte ratio and corticosterone in plasma and yolk are not considered to be reliable indicator. Body-surface temperature is considered a reliable indicator assessing laying hens exposed to ambient temperature. Panting and wings elevation are important adjustment behaviors during the 42 d long heat exposure.